2009
DOI: 10.1111/j.1574-0862.2009.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic efficiency in farm households: trends, explanatory factors, and estimation methods

Abstract: Factors explaining differences in economic efficiency between farms are of major interest to owners, managers, and other stakeholders as they strive to improve earnings and improve the chances of firm survival. This study is undertaken to improve our understanding of interfarm differences in, and opportunities to improve, farm household efficiency in utilizing their land, labor, and capital resources to achieve household objectives. The technical, allocative, and scale efficiencies of farm households are estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 19 publications
(30 reference statements)
6
22
0
Order By: Relevance
“…The agricultural economics literature has recognized the limitations with physical farm size measures and has used financial indicators, such as gross sales (Olson and Vu, 2009;Sumner and Wolf, 2002;Barry et al, 2001;Purdy et al, 1997). Financial measures can provide an indication of the physical size of the farm as a function of the amount of product sold while jointly representing the management capabilities of the principal operators as determined by the prices received for their products.…”
mentioning
confidence: 99%
“…The agricultural economics literature has recognized the limitations with physical farm size measures and has used financial indicators, such as gross sales (Olson and Vu, 2009;Sumner and Wolf, 2002;Barry et al, 2001;Purdy et al, 1997). Financial measures can provide an indication of the physical size of the farm as a function of the amount of product sold while jointly representing the management capabilities of the principal operators as determined by the prices received for their products.…”
mentioning
confidence: 99%
“…There is an emerging consensus that technical efficiency and overall performance of farms are influenced by farm size so that larger and more diversified farms are more productive or efficient than small farms 1 (Byrnes et al, 1987;Chavas and Aliber, 1993;Featherstone, Langemeier, and Ismet, 1997;Kalaitzandonakes, Wu, and Ma, 1992;Key, McBride, and Mosheim, 2008;Olson and Vu, 2009;Serra, Zilberman, and Gil, 2008;Weersink, Turvey, and Godah, 1990;Wu, Devadoss, and Lu, 2003). Byrnes et al (1987) investigated the relative technical performance of Illinois grain farms and observed that the major source of inefficiency was scale inefficiency, particularly for the large farms in the sample.…”
mentioning
confidence: 99%
“…These advances have not been included in many recent studies that have examined farm level technical efficiency of U.S. agriculture. An exception is the Olson and Vu (2009) study which estimated technical, allocative, and scale efficiencies of farms in southern Minnesota using the bootstrap output-based DEA approach. This paper used the Wilson (1998, 2000) smoothed bootstrap procedure to investigate the bias, variance, and confidence intervals for technical efficiency scores for the Kansas farm sector.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Th e results of the DEA procedures are often employed as the dependent variable in the further analysis searching socioeconomics sources of diff erences between the units' effi ciency (Assaf and Matawie 2009;Hu et al 2009;Olson and Vu 2009;Assaf and Agbola 2011). However when comparing the non-parametric approaches with those based on the regression analysis (RA), which are presented in Section 2, the diff erences between them are easily visible.…”
Section: Non-parametric Approachesmentioning
confidence: 99%